The geography of environmental innovation: a~critical review and agenda for future research - Sebastian Losacker; Hendrik Hansmeier; Jens Horbach; Ingo Liefner (Review of Regional Research, 2023)
This article provides a~critical literature review on the regional determinants of environmental innovation. The analysis of the relevant literature on supply-side factors, demand-side factors, and institutional factors reveals the importance of regional determinants in green technology development. Specifically, regional R&D collaborations, university-industry collaborations, and technological relatedness have positive effects on innovation activities in green domains. On the demand side, regional environmental awareness and demonstration effects play a~pivotal role in the emergence and diffusion of environmental innovations. Environmental regulations also induce environmental innovation, however, there is only limited evidence at the regional level. Our literature review has informed the development of an agenda for future research, which suggests three avenues for further investigation. Firstly, we recommend abandoning the simple green vs. non-green dichotomy and conducting more technology-sensitive studies on the determinants of environmental innovation. Secondly, we call for a~more sophisticated and critical engagement with regional institutions, with a~focus on both formal and informal institutions. Lastly, we propose a~demand-side turn in research on the regional determinants of environmental innovation in order to better understand their diffusion across space. Overall, our findings suggest that policymakers need to adopt a~more nuanced and comprehensive approach to eco-innovation policy, one that considers the spatial and multi-level governance challenges and promotes inclusive regional development.
Keywords: 910; Environmental innovation; Geography of innovation; Sustainability transitions; Regional development; Green technology